Technology and the Insurance Industry Re-configuring the Competitive Landscape - Cappiello, Antonella (Springer International Publishing, 2018)
The book analyzes the role of technology in the redefinition of the competitiveness of insurance markets. With a focus on the competitive challenges of InsurTech startup to the incumbent insurers, the book will discuss the strategic role of technology both in the development and in the distribution of insurance services and explore the customer relationship evolution following the digitalization of services offered. The book presents original theoretical and empirical contributions addressing how digitalization impacts the insurance environment and regulation, and how InsurTech development represents a threat for traditional companies, from Big Data analysis to digital devices, from personal interactivity to home automation systems development. The project's key benefit is up-to-date analysis of the competitiveness of technology usage in the insurance field, with particular reference to the distributive variable and to the future trends of the customer relationship in the short and medium-long term. The book will be of particular interest to scholars and students of insurance and financial technology.